Identifying Genes and Novel Variants Involved in Nonsyndromic Hearing Impairment, and Assessment of the Psychosocial Burden of Hearing Impairment in Cameroon - Wonkam, Tingang Edmond (Department of Pathology, 2022)
Background Hearing impairment (HI) is the most common sensory disability and occurs in about 1 per 1000 live births in high-income countries, with a much higher incidence of up to 6 per 1000 live births in sub-Saharan Africa (SSA). HI can be due to environmental or genetic causes, and in many cases, it is not possible to establish a definite aetiology. Hereditary HI contributes to 30% to 50% of HI cases in SSA. Hereditary HI can be syndromic or non-syndromic, depending on whether it is associated with additional abnormalities in other organs or not. Non-syndromic HI (NSHI) accounts for 70% of hereditary hearing loss, and is genetically highly heterogeneous, with approximately 170 loci and 121 genes identified to date. Studies in European and Asian populations have identified pathogenic variants in GJB2 (MIM: 121011), and GJB6 (MIM: 604418) genes as the major contributors to autosomal recessive NSHI (ARNSHI). The genetic aetiology of HI in Cameroon is unclear, as previous studies have found no contribution of GJB2 and GJB6 genes to NSHI in Cameroon. However, patients included in those studies consisted of both familial and isolated cases, therefore, underlying environmental/multifactorial causes in some cases cannot be excluded (especially for the isolated cases). Six loci for X-linked HI have been described to date, including DFNX3 (Xp21.2), where DMD is located. Variants in DMD in humans are known to be responsible for Duchenne muscular dystrophy (DMD; MIM: 310200), and Becker muscular dystrophy (BMD; MIM: 300376), an Xlinked recessive disorder. Previous studies have demonstrated that mdx mice, (an animal knockout model for DMD), have an increased threshold for hearing when compared to wildtype mice. However, the contribution of DMD to HI in humans has not been extensively studied. Besides, most of the previous studies on DMD were conducted in Caucasians, Asians, and Arabs; therefore, little is known about the features of this condition in Africans. Parents of children with HI tend to face challenges of parenting especially in terms of communication and social interaction. In Africa, parent's perceived causes of deafness vary from environmental factors to mysterious (“evil forces”) or superstitious beliefs. Also, the attitude of the society towards people with HI does not encourage their participation and involvement in the community, as they face overt discrimination. Aim and methods The aim of this project was to examine the genetic aetiologies of HI in the Cameroonian population, and undercover the challenges faced by persons with HI in Cameroon and their understanding of the causes of HI. This was addressed by 1) Establishing the current status of knowledge on HI in Africa (in terms of prevalence, aetiologies, and genetics aspects) with a particular focus on Cameroon, and assessing the contribution of connexin genes to HI in humans at a global level, through systematic literature reviews; 2) Revisiting the contribution of GJB2 and GJB6 genes to NSHI in 29 multiplex Cameroonian families with NSHI and with strong evidence of non-environmental causes, through targeted gene sequencing and specific multiplex polymerase chain reaction (PCR); 3) Using multiplex ligand-dependent probe amplification (MLPA) technique to investigate the most common variants associated with DMD in Cameroon and assess their possible implication in HI in humans; 4) Performing whole exome sequencing (WES) on 2 Cameroonian multiplex families with NSHI and who tested negative for pathogenic variants in GJB2 and GJB6, to identify the underlying causative genes; 5) Performing in-depth interviews to gain an understanding of the challenges faced by people with HI in Cameroon, their understanding of the causes of hearing impairment (HI), and how challenges could be remedied to improve the quality of life of persons with HI. Results Literature reviews Our first systematic review showed that HI is a public health issue in Cameroon, especially in the elder population where the prevalence of HI is 14.8% in people aged 50 years and more. Environmental factors, including meningitis, impacted wax, and age-related disorders are the leading aetiologies of HI in Cameroon as in many other SSA countries, contributing 52.6% to 62.2% of HI cases. Hereditary HI comprises 0.8% to 14.8% of all cases in Cameroon, and in 32.6% to 37% of HI cases, the origin remains unknown. This contrasts with findings from highincome countries where hereditary HI constitutes the main aetiology of HI, contributing to approximately 50% of cases. NSHI is the most frequent clinical entity and accounts for 86.1% to 92.5% of cases of hereditary HI in the Cameroonian population. No pathogenic variant was described in GJB6 gene, and the prevalence of pathogenic variants in GJB2 ranged from 0% to 0.5%. The prevalence of pathogenic variants in other known NSHI genes was with type 2 Waardenburg syndrome, and three cases of type 2 Usher syndrome were identified in one family. By direct gene sequencing of the coding region of GJB2, no variants were found in any of the 29 families with NSHI. Additionally, through a specific multiplex PCR, the GJB6- D3S1830 deletion which contributes to 9.7% of NSHI cases in Europeans was not identified in any of the patients with HI. Subsequently, a total of 17 males with DMD from 14 families were recruited, aged 14 ± 5.1 (8–23) years. The mean age at onset of symptoms was 4.6 ± 1.5 years, and the mean age at diagnosis was 12.1 ± 5.2 years. Proximal muscle weakness was noted in all patients and calf hypertrophy in the large majority of them (88.2%; 15/17). Flexion contractures were particularly frequent on the ankle (85.7%; 12/14). Wasting of the shoulder girdle and thigh muscles was present in 50% (6/12) and 46.2% (6/13) of patients, respectively. No patient presented with HI. The MLPA found that deletions of at least one exon in DMD occurred in 45.5% of patients (5/11), while duplications were observed in 27.3% (3/11). Both variant types were clustered between exons 45 and 50, and the proportion of de novo variant was estimated at 18.2% (2/11). Whole exome sequencing We submitted DNA samples from five members of a multiplex non-consanguineous Cameroonian family segregating prelingual and progressive ARNSHI for WES. We identified novel bi-allelic compound heterozygous pathogenic variants in CLIC5 (MIM: 607293). The variants identified, i.e. the missense [NM_016929.5:c.224T>C; p.(Leu75Pro)] and the splicing (NM_016929.5:c.63+1G>A), were validated using Sanger sequencing in all seven available family members and co-segregated with HI in the three family members with HI. The three affected individuals were compound heterozygous for both variants, and all unaffected individuals were heterozygous for one of the two variants. Both variants classify as pathogenic by the American College of Medical Genetics (ACMG) guidelines for classification of variants and are absent from the genome aggregation database (gnomAD), UK10K, Greater Middle East (GME) database, and the Single Nucleotide Polymorphism Database (dbSNP), as well in 122 healthy controls from Cameroon. We also did not identify these pathogenic variants in 118 unrelated sporadic cases of NSHI from Cameroon. A second multiplex family was also screened through the use of WES, followed by direct Sanger sequencing in additional patients and control participants. We identified a heterozygous novel missense variant [NM_001174116.2:c.918G>T; p.(Gln306His)] in DMXL2 (MIM:612186) which was transmitted in an autosomal dominant manner, and co-segregates with congenital/prelingual profound to total non-syndromic sensorineural HI in a family from Cameroon. The described family showed a variable expressivity of the HI phenotype. The p.(Gln306His) variant which substitutes a highly conserved glutamine residue is predicted deleterious by various bioinformatics tools and is absent from several genome databases including genome aggregation database (gnomAD), and trans-omics for precision medicine (TOPMed) database. This variant was neither found in 121 healthy controls without personal or family history of HI, nor 112 sporadic cases of NSHI from Cameroon. Our study identified novel variants in CLIC5 and DMXL2 in two Cameroonian families, and provided only the second report of variants in these genes worldwide; thus, strengthening the case for these two genes as candidate genes for NSHI in humans. The psychosocial burden of HI We performed in-depth interviews with 10 HI professionals (healthcare workers, and educationists), and 10 persons affected by HI (persons with HI, and caregivers). The results show that in this study population, the cause of HI is attributed to a variety of causes, including genetics, environmental factors, and a spiritual curse. There were reported cases of stigma and discrimination with persons with HI in the Cameroonian population sometimes seen as having a “mental disorder”. Our participants also highlighted the difficulty that persons with HI have in accessing the necessary education and healthcare services, and suggested the need for policymakers and researchers to develop strategies to improve the social integration of persons with HI and their access to basic social services. This includes 1) Increased awareness amongst the general population, 2) the establishment of more special schools, and 3) building and equipping facilities for proper management of HI. Conclusions Our project confirms that variants in GJB2 and GJB6 genes do not contribute significantly to NSHI in the Cameroonian population. Also, variants in DMD that were shown to be associated with an increased hearing threshold in mice, do not seem to be implicated in HI in Cameroon, neither in previous human studies (although they did not objectively assess hearing using standardized testing methods). Despite the first symptoms of DMD occurring in infancy, the diagnosis is frequently made later in adolescence, indicating an underestimation of the number of cases of DMD in Cameroon. Future screening of deletions and duplications in patients from Cameroon should focus on the distal part of the DMD gene. Subsequently, this study successfully identified the candidate genes in two Cameroonian multiplex families with NSHI through the use of WES, and thus highlights the efficacy of next-generation sequencing techniques in resolving HI cases in Cameroonians and in cases where no pathogenic variants are found in common HI-genes. Additionally, our project which confirms that CLIC5 and DMXL2 genes are associated with HI in humans advocate for the inclusion of these two genes in diagnostic gene panels for NSHI in clinical settings. Last, this study shows the difficult social interaction and access to proper management faced by persons with HI in Cameroon, and highlights the need to educate populations on the causes of HI for a better acceptance of persons with HI in the Cameroonian society.